Advances in understanding erythropoiesis: evolving perspectives. (5th February 2016) - Nandakumar, Satish K.; Ulirsch, Jacob C.; Sankaran, Vijay G.
Summary: Red blood cells (RBCs) are generated from haematopoietic stem and progenitor cells (HSPCs) through the step‐wise process of differentiation known as erythropoiesis. In this review, we discuss our current understanding of erythropoiesis and highlight recent advances in this field. During embryonic development, erythropoiesis occurs in three distinct waves comprising first, the yolk sac‐derived primitive RBCs, followed sequentially by the erythro‐myeloid progenitor (EMP) and HSPC‐derived definitive RBCs. Recent work has highlighted the complexity and variability that may exist in the hierarchical arrangement of progenitors responsible for erythropoiesis. Using recently defined cell surface markers, it is now possible to enrich for erythroid progenitors and precursors to a much greater extent than has been possible before. While a great deal of knowledge has been gained on erythropoiesis from model organisms, our understanding of this process is currently being refined through human genetic studies. Genes mutated in erythroid disorders can now be identified more rapidly by the use of next‐generation sequencing techniques. Genome‐wide association studies on erythroid traits in healthy populations have also revealed new modulators of erythropoiesis. All of these recent developments have significant promise not only for increasing our understanding of erythropoiesis, but also for improving our ability to intervene when RBC production is perturbed in disease.